Feline Cryptococcus in Malaysia: a first report - Arshad, Habibah; Abdul Mutalib, Abdul Rahim; Bejo, Mohd Hair; Heng, Hock Gan (Veterinary Association Malaysia, 2009)
Cryptococcosis was diagnosed in a Domestic Shorthair cat showing upper respiratory signs of sneezing, stertorous, bilateral mucopurulent nasal discharges and swelling over the frontal area and nasal bridge. The diagnosis was made based on cytology, culture and histopathology. Treatment with itraconazole was unsuccessful because of poor client compliance. To our knowledge, this is the first report of cryptococcosis in cats in Malaysia.